2014
DOI: 10.3892/br.2014.390
|View full text |Cite
|
Sign up to set email alerts
|

Differential upregulation of the hypothetical transmembrane protein 66 (TMEM66) in multiple sclerosis patients with potential inflammatory response

Abstract: Abstract. The prevalence of multiple sclerosis (MS) in the Gulf region has markedly increased during the last decade, but the mechanisms of the disease have not been investigated. The present study aimed to understand the molecular processes involved in the disease development of the recently emerged MS in this population using microarray technology to investigate differentially-expressed novel genes in MS patients compared to healthy-matched subjects. The expression of the upregulated genes was confirmed by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
4
3
Order By: Relevance
“…IL‐6 acts as an important mediator for inflammation, and overexpressed IL‐6 has a potential risk which may cause additional cell death, and neurological dysfunction . Upregulated Anxa3 and induced proinflammatory cytokines TNF‐α and IL‐6 were both shown in patients with multiple sclerosis, which indicated that Anxa3 may induce TNF‐α, and IL‐6 . There was a study also found that SAP mice had higher AMS levels, MPO activity in the lung tissues, and value of W/D .…”
Section: Discussionmentioning
confidence: 91%
“…IL‐6 acts as an important mediator for inflammation, and overexpressed IL‐6 has a potential risk which may cause additional cell death, and neurological dysfunction . Upregulated Anxa3 and induced proinflammatory cytokines TNF‐α and IL‐6 were both shown in patients with multiple sclerosis, which indicated that Anxa3 may induce TNF‐α, and IL‐6 . There was a study also found that SAP mice had higher AMS levels, MPO activity in the lung tissues, and value of W/D .…”
Section: Discussionmentioning
confidence: 91%
“…However, our results are in discrepancy with a previous study that found that SARAF may be preferentially expressed in patients with multiple sclerosis [ 43 ]. The study showed that SARAF induced the expression of pro-inflammatory cytokines, but not anti-inflammatory cytokines [ 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results are in discrepancy with a previous study that found that SARAF may be preferentially expressed in patients with multiple sclerosis [ 43 ]. The study showed that SARAF induced the expression of pro-inflammatory cytokines, but not anti-inflammatory cytokines [ 43 ]. These findings are partially supported with findings that indicate that SARAF contributes to T-cell activation through the promotion of TCR-mediated signaling via Ca 2+ –calcineurin–nuclear factor of the activated T-cells (NFAT) pathway [ 42 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In summary, the dual regulatory effect of SARAF on CRAC channel activity presented in this work sheds light on a poorly characterized step during CRAC channel activation and provides an important framework for understanding the physiological role of SARAF in different cell types and its potential involvement in different pathophysiological conditions, including pancreatitis ( Son et al, 2019 ), cancer ( Romanuik et al, 2009 ; Iżykowska et al, 2017 ), neurodegenerative diseases ( Iżykowska et al, 2017 ; Taha et al, 2015 ; Twine et al, 2011 ), and cardiovascular diseases ( Yang et al, 2019 ; Dai et al, 2018 ; Camargo and Azuaje, 2008 ; Sanlialp et al, 2020 ; La Russa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 86%